Deurbanizing for conservation and adapting: framing ecological restoration as a nature-based solution in La Pletera salt marsh, Catalonia (Spain) - Diego Pereira Lindoso; Dani Boix; Anna Ribas; Jordi Bou; Xavier D. Quintana (Frontiers in Water)
Tackling climate change and biodiversity loss are two of the great global challenges of the 21st century. The nature-based solutions (NbS) approach creates an opportunity to meet efforts on the two agendas while producing other co-benefits beyond climate resilience and biodiversity conservation. This opportunity becomes even more relevant in areas with both high climate vulnerability and special interest for conservation. Coastal wetlands in the Mediterranean basin are under severe threat from urban sprawl, mass tourism and climate change. Coastal lagoons, dune systems and halophilic ecosystems are considered as priority habitats of community interest for conservation by the European Habitats Directive. In the Catalan coast, these ecosystems are fragmented and isolated, and ecological protection and restoration efforts are essential. In this context, the present work analyzes the case of de-urbanization and ecological restoration of La Pletera salt marsh by the Life Pletera project (2014–2018), interpreting it within an NbS approach and assessing its effectiveness as a strategy for climate adaptation and biodiversity conservation. The analysis brings insights for the effectiveness assessment of the project during the first years after implementation, gathers elements on the factors and constraints that made its implementation possible and reflects on future challenges so that its effectiveness is lasting in the medium and long term.